Lexical and grammatical features of English analytical forms and the ways of their translation into Belarusian - Brutskaya, Alina A. (Journal of the Belarusian State University. Philology, 2019)
The article deals with the specificity of English analytical forms and the ways of their translation into Belarusian. It defines the concept of the analytical forms. Lexical, grammatical and structural peculiarities of analytical forms are found. Typology of English analytical forms is considered. The research looks at the stories by A. C. Doyle and their translations of different authors. The main types of morphological transformations of the analytical forms of tense from English into Belarusian are outlined. Special attention is paid to the necessity of determination of the main translation methods of English analytical forms into Belarusian.
Keywords: analytical forms; English analytical forms; analytical verb forms of tense; translation; English to Belarusian translation; morphological transformations